Inducing secondary metabolite production by the soil-dwelling fungus Aspergillus terreus through bacterial co-culture. (June 2015) - Chen, Huiqin; Daletos, Georgios; Abdel-Aziz, Mohamed S.; Thomy, Dhana; Dai, Haofu; Brötz-Oesterhelt, Heike; Lin, Wenhan; Proksch, Peter
Graphical abstract: Highlights: We isolated Aspergillus terreus from the sediment of a hyper saline lake in Egypt. The fungus was co-cultured either with Bacillus subtilis or with Bacillus cereus . We found an up to 34-fold increase in the fungal natural product accumulation. Two new butyrolactone derivatives were obtained after co-cultivation of the fungus. The structures were determined by extensive analysis of the spectroscopic data. Abstract: The soil-dwelling fungus Aspergillus terreus was isolated from sediment collected from the lake of Wadi EI Natrun in Egypt. Co-cultivation of A. terreus with the bacteria Bacillus subtilis and Bacillus cereus on solid rice medium resulted in an up to 34-fold increase in the accumulation of constitutively present fungal natural products (4 –15 ) compared to axenic cultures of A. terreus . The fungal products included two new butyrolactone derivatives, isobutyrolactone II (1 ) and 4-O-demethylisobutyrolactone II (2 ), together with the known N-(carboxymethyl)anthranilic acid (3 ) that were not present in axenic fungal controls and were only detected during co-cultivation with B. subtilis or with B. cereus . The structures of all compounds were unambiguously elucidated by 1D and 2D NMR spectroscopy, and by HRESIMS measurements, as well as by comparison with the literature. In a second set of experiments, A. terreus was co-cultured with Streptomyces lividans and with Streptomyces coelicolor . These co-cultivation experiments failed to induce fungal natural product accumulation in contrast to co-cultures with Bacillus sp. Compounds 5 and 14 showed weak inhibition of B. cereus with minimal inhibitory concentrations (MICs) of 64 μg/mL, whereas only 8 showed moderate cytotoxicity against the murine lymphoma (L5178Y) cell line with inhibition of 80% at a dose of 10 μg/mL.